2021
DOI: 10.1038/s42003-020-01625-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the immune environment in clear cell renal carcinoma by single-cell genomics

Abstract: Clear cell renal cell carcinoma (ccRCC) is one of the most immunologically distinct tumor types due to high response rate to immunotherapies, despite low tumor mutational burden. To characterize the tumor immune microenvironment of ccRCC, we applied single-cell-RNA sequencing (SCRS) along with T-cell-receptor (TCR) sequencing to map the transcriptomic heterogeneity of 25,688 individual CD45+ lymphoid and myeloid cells in matched tumor and blood from three patients with ccRCC. We also included 11,367 immune cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(186 citation statements)
references
References 62 publications
11
174
0
1
Order By: Relevance
“… 17 It has been found that KIRC tissue is often infiltrated by lymphocytes (T cells, B cells, and natural killer cells), macrophages, and dendritic cells. 33 , 34 The activated CD8+ T cells and activated dendritic cells were associated with the poor prognosis of KIRC, and the infiltrating CD4+ T cells could enhance KIRC cell proliferation. Infiltrating macrophages increased KIRC cell invasion via alteration of EMT and increasing the stem-cell-like population.…”
Section: Discussionmentioning
confidence: 99%
“… 17 It has been found that KIRC tissue is often infiltrated by lymphocytes (T cells, B cells, and natural killer cells), macrophages, and dendritic cells. 33 , 34 The activated CD8+ T cells and activated dendritic cells were associated with the poor prognosis of KIRC, and the infiltrating CD4+ T cells could enhance KIRC cell proliferation. Infiltrating macrophages increased KIRC cell invasion via alteration of EMT and increasing the stem-cell-like population.…”
Section: Discussionmentioning
confidence: 99%
“…The single-cell RNA-seq data processing was described previously ( 27 ). The cell clusters were annotated manually based on previous knowledge and information from literatures ( 28 , 29 ). Expression profiling of the genes were depicted by heatmap and violin plot using the function “FeaturePlot” and “VlnPlot.”…”
Section: Methodsmentioning
confidence: 99%
“…D. Prediction of cell types. Cell types were predicted using singleR R package 92 ; normalized correlation values for predicted immune cell phenotypes are shown. Cluster of columns based on Ward.D2 distance between normalized correlation values across all pure immune cell populations in the Immgen database 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Results were visualized using the ggplot2 R package (version 3.2.1). Single-cell normalized enrichment scores were calculated using the escape (v1.0.1) R package 92 . From this analysis, differentially expressed ligand and receptor between myocarditic and healthy controls for indicated cell types were extracted to use for the size/count of the dot plot.…”
Section: Methodsmentioning
confidence: 99%